1987
DOI: 10.1038/sc.1987.62
|View full text |Cite
|
Sign up to set email alerts
|

The diagnosis and management of post traumatic syringomyelia

Abstract: SummaryWe have reviewed 21 cases with the clinical diagnosis of Post Traumatic Syringo myelia (P. T.S.). FzJteen of these cases had proven syrinx formation on Contrast Computed Tomography (C.C.T.) and the other 6 had obviously abnormal cords. A much earlier onset of P. T.C.M. was found in complete spinal injuries than in incomplete ones. We have discussed the technique of contrast computed tomography used at this hospital, its value in the diagnosis of this condition and its ability to define actual spinal cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0
1

Year Published

1993
1993
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 7 publications
1
25
0
1
Order By: Relevance
“…Sgouros and Williams 17 found that 78% of syringomyelia patients had a thoracolumbar spinal injury, whereas El Masry et al 5 and PerrouinVerbe et al 9 concluded that cavities form more commonly in thoracic compared with cervical spinal cord injury patients. In contrast, Rossier et al, 14 Lyons et al, 18 and Vannemreddy et al 6 found that syringomyelia was more commonly associated with cervical spinal cord injury. Such observations are consistent with theories suggesting that the development of syringomyelia is associated with an increase in CSF pressure, because the mid-cervical spinal canal and the subarachnoid space are both relatively narrower than the thoracolumbar canal, as shown by Yarkony et al 19 We also investigated whether syringomyelia development correlated with the severity of neurological injury.…”
Section: Discussionmentioning
confidence: 90%
“…Sgouros and Williams 17 found that 78% of syringomyelia patients had a thoracolumbar spinal injury, whereas El Masry et al 5 and PerrouinVerbe et al 9 concluded that cavities form more commonly in thoracic compared with cervical spinal cord injury patients. In contrast, Rossier et al, 14 Lyons et al, 18 and Vannemreddy et al 6 found that syringomyelia was more commonly associated with cervical spinal cord injury. Such observations are consistent with theories suggesting that the development of syringomyelia is associated with an increase in CSF pressure, because the mid-cervical spinal canal and the subarachnoid space are both relatively narrower than the thoracolumbar canal, as shown by Yarkony et al 19 We also investigated whether syringomyelia development correlated with the severity of neurological injury.…”
Section: Discussionmentioning
confidence: 90%
“…A higher incidence of PTS in quadriplegics compared with paraplegics has been reported in other series. 19,27,28 so that the matter remains unresolved. Our data suggest that lumbar spinal cord injury may be associated with later onset of PTS compared with higher injuries.…”
Section: Level Of Spinal Cord Injurymentioning
confidence: 98%
“…The close relationship between the syringomyelic cavity and the vertebral fracture supports the thesis that the latter is a relevant factor for the development of the cavity, as occurs in the case we present. 12,13 Post-traumatic syringomyelia appears both in patients submitted to conservative therapy (as in our patient) and in those who have undergone surgery in the acute phase of the spinal cord injury; a similar incidence has been described for both groups. No large series comparing both groups exists in the literature, and even the series with surgically-treated patients are scarce.…”
Section: Discussionmentioning
confidence: 67%
“…At present, the preferred procedure is to establish a shunt between the syringomyelic cavity and a low pressure Post-traumatic syringomyeliasystem implanted at thoracic or abdominal level, resulting in a much lower incidence of obstruction in comparison to previous types of shunt. 13,17,18 In general, the results with surgery are favourable. All series agree as to the relief of pain in almost all cases, followed by improvement of the motor de®cit; the least observed improvement is the recovery of sensitivity, although the series presented by Lyons 13 and El Masry 3 describe a postoperative recovery of sensitivity of 91% and 73%, respectively.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation